Expression of SARS-CoV-2 receptor "ACE2" in human pancreatic β cells: to be or not to be!. Issue 5 (3rd September 2021) - El-Huneidi, Waseem; Hamad, Mawieh; Taneera, Jalal
ABSTRACT: The current COVID-19 pandemic, which continues to spread across the globe, is caused by severe acute respiratory syndrome coronavirus (SARS-Cov-2). Soon after the pandemic emerged in China, it became clear that the receptor-binding domain (RBD) of angiotensin-converting enzyme 2 ( ACE2 ) serves as the primary cell surface receptor for SARS-Cov-2. Subsequent work has shown that diabetes and hyperglycemia are major risk factors for morbidity and mortality in COVID-19 patients. However, data on the pattern of expression of ACE2 on human pancreatic β cells remain contradictory. Additionally, there is no consensus on whether the virus can directly infect and damage pancreatic islets and hence exacerbate diabetes. In this mini-review, we highlight the role of ACE2 receptor and summarize the current state of knowledge regarding its expression/co-localization in human pancreatic endocrine cells. We also discuss recent data on the permissiveness of human pancreatic β cells to SARS-Cov-2 infection.